104k views
0 votes
(ax-bx)/(x+c)=d solve for x

User Tyler Day
by
5.8k points

2 Answers

1 vote

Answer:

x =
(cd)/(a-b-d)

Explanation:

Given


(ax-bx)/(x+c) = d ← multiply both sides by (x + c)

ax - bx = d(x + c) ← distribute parenthesis

ax - bx = dx + cd ( subtract dx from both sides )

ax - bx - dx = cd ← factor out x from each term on the left side

x(a - b - d) = cd ← divide both sides by (a - b - d)

x =
(cd)/(a-b-d)

User Amir Khorsandi
by
5.9k points
0 votes

Answer:

Explanation:

(ax-bx)/(x+c)=d

ax - bx = d * (x+c)

ax - bx = dx + cd

ax - bx - dx = cd

x * (a-b-d) = cd

x = cd/(a-b-d)

User Denisafonin
by
5.8k points